FRI0595-HPR Reduction of Sedentary Behaviour in Patients with Rheumatoid Arthritis. A Randomized Feasibility Study. (10th June 2014) - Thomsen, T.; Aadahl, M.; Hetland, M.L.; Beyer, N.; Loeppenthin, K.; Esbensen, B.A.
Abstract : Background: Patients with rheumatoid arthritis (RA) are more sedentary than the general population and have an increased risk of cardiovascular disease. Reduction of sedentary behaviour (SB) has been suggested as a means for improvement of health in patients with chronic diseases and mobility problems. Short-term intervention studies have demonstrated that SB can be reduced by behavioural interventions in healthy sedentary populations. However, it remains unexplored whether this also applies for patients with RA. Objectives: To evaluate the feasibility of a 4-month multidimensional behavioural intervention targeting reduction of SB in patients with RA. This included identification of barriers for enrolment and intervention adherence and problems regarding screening, recruitment, randomization and logistics in general. Methods: A randomized, controlled trial (1:1) with two parallel groups. RA patients >18 years of age with self-reported daily leisure time sitting >4 hours and Health Assessment Questionnaire (HAQ) score <2.5 were consecutively recruited from a rheumatology outpatient clinic. Medical journals were screened for diagnosis and HAQ score and an information letter was sent to eligible patients. Those invited were later screened for daily leisure time sitting by a telephone interview. The 4-month intervention included 1) 3 individual motivational counselling sessions of 60-90 minutes with a health professional and 2) individual SMS-reminders aiming at reducing daily sitting time. The control group was encouraged to continue usual lifestyle. The primary outcome, daily sitting time was assessed at baseline and at 4 months using an ActivPAL3™ activity monitor worn on the right thigh for seven consecutive days. Results: In total, 87 patients were invited and screened before 20 met eligibility criteria and consented. Reasons for declining study participation were mostly flares, lack of time and co-morbidities. Age and disease duration in the intervention group vs. the control group (mean (SD; range)): 65 years (9;46-76) vs. 54 years (14;34-81) and 14 years (11;3-41) vs. 9 years (14;1-46). At baseline the mean daily sitting time was 10.70 hours (1.80) vs. 9.50 hours (1.50). At follow-up the mean change in daily sitting time was minus 0.30 h/day (95% CI -1.70-1.07) in the intervention group and plus 0.15 h/day (95% CI -0.95-1.25) in the control group. The between-group difference in change was -0.45 h/day (95% CI -2.10-1.20) in favour of the intervention group. One patient from the control group dropped out before follow-up (due to RA flare). All patients in the intervention group completed the intervention. All procedures in relation to implementation of the trial protocol were feasible. Conclusions: Our results showed that the study protocol was feasible and the results were promising, indicating that the intervention may reduce SB. The sample size was, as expected, too small to have statistical power. An RCT study with a larger population is ongoing. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3097